Treatment of Neck Muscle Pain and Tension with TPG Therapy - Danuditya Purna Atmaja (Jurnal EduHealth, 2023)
Neck pain is pain that appears in the back of the neck, right neck, left neck, or front neck. Neck pain generally occurs due to pulled neck muscles, pinched nerves, or calcification of the joints. In general, neck pain or neck pain is not a serious condition that needs to be watched out for. This condition can heal in a few days or a few weeks without special treatment. However, there are also neck pains that appear as a symptom of certain diseases. Meanwhile, muscle tension in the neck is the most common cause of muscle pain. Usually this muscle tension is triggered by: Poor posture when walking, standing or sitting. Incorrect sleeping position or uncomfortable pillow use. In this study, the focus is on how to deal with or treat neck muscle pain and tension with acupressure, hitting and motion therapy. So in other words this research is to examine the activities of handling pain and tension that often occur in the neck muscles with the acupressure, motion and neck therapy methods. Besides that, you can find out how far the effectiveness of the method is. The hope of the researchers themselves is to get maximum results and gain new knowledge from this activity and to provide references for other researchers in the future.